DETERMINANTS OF HYDROPOWER GENERATION IN ETHIOPIA - Kwakwa, P. A.; Alhassan, H. (UDS International Journal of Development, 2018)
Even though the share of hydropower in electricity has been increasing in recent times for the Ethiopian economy, less than 3% of the hydropower potential has been developed. Meanwhile, the country aims to achieving middle-income status by 2025 alongside a reduction in emission of gases that contribute to climate change. This requires the use of more renewable energy sources particularly hydro source. This study examined the drivers of hydro power generation in Ethiopia using annual time series data for the period 1981- 2014. Estimations from the Fully Modified Ordinary Least Square (FMOLS) and Canonical Cointegrating Regression (CCR) revealed that Ethiopia’s hydropower generation is influenced positively by price, technology and environmental degradation while cost of production reduces it. Based on these findings the study suggests that, more technology investment is needed in the country’s hydropower sector to enhance production. Keywords: Renewable Energy, Electricity, Hydro Power, FMOLS, CCR, Ethiopia